Laparosacopic management with combination of fatty meal and methylen-blu for chylous leak after a left para-aortic paraganglioma excision. Issue 12 (29th December 2020) - Cupellini, Curzio; Alemanno, Giovanni; Bottari, Andrea; Bella, Annamaria Di; Bruscino, Alessandro; Martellucci, Jacopo; Bergamini, Carlo; Pantalone, Desiree; Prosperi, Paolo
Abstract: We report a case of chylous leak recognized post-operatively after abdominal surgery for left para-aortic paraganglioma in a young female with a history of open botallo's duct. Conservative measures failed to control the leak and the patient is not eligible for sclerotisation. Laparoscopic exploration with intralipidand methylen blue injection through an orogastric tube revealed the leaking area near the superior mesenteric vein behind the Traitz, and this was ligated with non-asorbable suture and placement of acrylic glue. The patient was discharged the 7th post-operative day after removal of the drainage which appeared to supply <100 cc of serum material. Outpatient control was successful and the patient is actually in good conditions.